New approaches to enhance hydrogen production from glycerol by Escherichia coli - Poladyan, A. A. (ՀՀ ԳԱԱ հրատ.)
Glycerol as a waste material of biodiesel and other industries can be considered for biological hydrogen (H2) production. Upon Escherichia coli glycerol fermentation formate, ethanol and etc. are produced. Formate decomposition by fromatehydrogenaselyase enzymes lead to H2 and CO2 formation. Four [NiFe] Hydrogenase (Hyd) enzymes are involved in this process for activity of which heavy metals can be required.The results obtained identify the conditions when reductive conditions has essential role for H2 production in E. coli upon glycerol fermentation. Moreover, mixed carbons or addition of some heavy metal ions enhance H2 generation. These approaches might be applied to regulate H2 metabolism upon bacterial industrial wastes (glycerol) fermentation resulting enhanced H2 production. Глицерол – отход биодизельного и других производств может быть успешно использован для получения биоводорода (H2). В процессе брожения глицерола Escherichia coli выделяет муравьиную кислоту, этанол и другие конечные продукты. Фермент формиат водород лиаза трансформирует муравьиную кислоту до H2 и СО2. Четыре [NiFe] гидрогеназы, для активации которых необходимы ионы металлов, участвуют в этом процессе. Полученные результаты свидетельствуют о том, что среда с восстановленным редокс потенциалом существенна при брожении E. сoli для производства H2. Данные подходы могут быть применены для регулирования метаболизма H2 у бактерий E. сoli, содействуя промышленному получению био- водорода из отходов (глицерола).Գլիցերոլը որպես կենսադիզելի և այլ արտադրությունների թափոն կարող է հաջողությամբ կիրառվել կենսաջրածնի (H2) ստացման համար: Escherichia coli-ին գլիցերոլի խմորման ժամանակ արտադրոում է մրջնաթթու, էթանոլ և այլ վերջնանյութեր: Մրջնաթթու ջրածինլիազ ֆերմենտը մրջնաթթուն վերածում է մինչև H2-ի և CO2-ի: Չորս [NiFe] հիդրոգենազ (Հիդ) ֆերմենտներ, որոնց ակտիվության համար մետաղներ են անհրաժեշտ, մասնակցում են այդ գործընթացին: Ստացված տվյալները վկայում են, որ վերականգնված ռեդօքս պոտենցիալով միջավայրը էական է գլիցերոլի խմորման ընթացքում E. coli -ի H2 արտադրության համար: Խառը ածխածնի աղբյուրները և որոշ ծանր մետաղներ խթանում են H2-ի արտադրությունը: Այս մոտեցումները կարող են կիրառվել H2-ի նյու¬թափոխանակության կարգավորման նպատակով և կնպաստեն արդյունաբերական թափոններից (գլիցերոլից) կենսաջրածնի ստացման խթանմանը:
Keywords: Biology